Potentialités et limites de la notion de capital environnemental au regard de la crise environnementale contemporaine - Josselin Guyot-Téphany (Éditions en environnement VertigO, 2018)
The introduction of ‘environmental capital’ by the research laboratory GEOLAB is testament to the will of researchers of human geography to face together common difficulties in order to deal with environmental issues. The special framework derived from this approach aims to analyze the current social-environmental dynamic in great depth/in all of its complexity. Using tools from the French sociology of Pierre Bourdieu in an environmental context, the idea of the environment is perceived as a social and political resource used by actors within the structuring of contemporary societies. This theorical paper investigates the notion of ‘environmental capital’ to identify heuristic benefits and potential weaknesses in the reflexive framework of the environmental crisis. Firstly we’ll bring up the issue of their origins in social sciences. Secondly we will consider the means of appreciating Bourdieu’s concept in the environmental context with particular attention drawn to solving challenging and theorical problems. By these efforts we aim to discuss, for example, the assumption of universality in using this approach, the consistency of environmental values which inspire discourse and practices, or even the convenience of the scientific relationship between the dominant/dominated in understanding conflict situations. Finally, after having discussed some of the limits of the constructivist approach in relation to the ‘environmental capital’, we then will propose to mix means of interpreting the socio-environmental dynamic with alternative epistemological orientation to go beyond the duality between Nature and Culture in Environmental Geography.